Exposure to Sound Vibrations Lead to Transcriptomic, Proteomic and Hormonal Changes in Arabidopsis - Ghosh, Ritesh (Sci Rep, 2016)
Sound vibration (SV) is considered as an external mechanical force that modulates plant growth and development like other mechanical stimuli (e.g., wind, rain, touch and vibration). A number of previous and recent studies reported developmental responses in plants tailored against SV of varied frequencies. This strongly suggests the existence of sophisticated molecular mechanisms for SV perception and signal transduction. Despite this there exists a huge gap in our understanding regarding the SV-mediated molecular alterations, which is a prerequisite to gain insight into SV-mediated plant development. Herein, we investigated the global gene expression changes in Arabidopsis thaliana upon treatment with five different single frequencies of SV at constant amplitude for 1 h. As a next step, we also studied the SV-mediated proteomic changes in Arabidopsis. Data suggested that like other stimuli, SV also activated signature cellular events, for example, scavenging of reactive oxygen species (ROS), alteration of primary metabolism, and hormonal signaling. Phytohormonal analysis indicated that SV-mediated responses were, in part, modulated by specific alterations in phytohormone levels; especially salicylic acid (SA). Notably, several touch regulated genes were also up-regulated by SV treatment suggesting a possible molecular crosstalk among the two mechanical stimuli, sound and touch. Overall, these results provide a molecular basis to SV triggered global transcriptomic, proteomic and hormonal changes in plant.